Stabilisation of 2, 6‐Diarylpyridinium Cation by Through‐Space Polar–π Interactions. Issue 21 (15th April 2014) - Padial, Joan Simó; de Gelder, René; Fonseca Guerra, Célia; Bickelhaupt, F. Matthias; Mecinović, Jasmin
Abstract: The through‐space polar–π interactions between pyridinium ion and the adjacent aromatic rings in 2, 6‐diarylpyridines affect the p K a  values. Hammett analysis illustrates that the basicity of pyridines correlates well with the sigma values of the substituents at the para  position of the flanking aryl rings. Abstract : The through‐space polar–π interactions between pyridinium ion and the adjacent aromatic rings in 2, 6‐diarylpyridines affect the p K a  values. Hammett analysis illustrates that the basicity of pyridines correlates well with the sigma values of the substituents at the para  position of the flanking aryl rings (see figure).